2004
DOI: 10.1016/j.neuroimage.2004.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Beyond common resources: the cortical basis for resolving task interference

Abstract: Recent studies have suggested that declining inhibitory control observed during simultaneous increases in working memory (WM) demands may be due to sharing common neural resources, although it is relatively unclear how these processes are successfully combined at a neural level. Event-related functional MRI was used to examine task performance that required inhibition of varying numbers of items held in WM. Common activation regions for WM and inhibition were observed and this functional overlap may constitute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
43
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 79 publications
11
43
0
Order By: Relevance
“…It is also a novel examination of the effects of brief practice of the WMI task on general cognitive task processes and the effects of itemspecific practice occurring as a result of repeated exposure to the same stimuli over a single block of trials. We observed that withholding a prepotent response to items held in WM activated a predominantly right-hemisphere network of regions, including middle and inferior frontal cortex, insula, midline frontal areas (SMA, pre-SMA, and ACC), inferior parietal cortex, striatum and thalamus, consistent with Hester et al (2004b) and previous neuroimaging studies of response inhibition (e.g., Garavan et al, 1999;Kelly et al, 2004;Liddle et al, 2001;Rubia et al, 2003;Watanabe et al, 2002). Errors of commission activated lateral frontal, midline, and insular areas also consistent with previous studies (Hester et al, 2004b;Holroyd et al, 2004;Ullsperger and Von Cramon, 2003;Ridderinkhof et al, 2004;Kiehl et al, 2000).…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…It is also a novel examination of the effects of brief practice of the WMI task on general cognitive task processes and the effects of itemspecific practice occurring as a result of repeated exposure to the same stimuli over a single block of trials. We observed that withholding a prepotent response to items held in WM activated a predominantly right-hemisphere network of regions, including middle and inferior frontal cortex, insula, midline frontal areas (SMA, pre-SMA, and ACC), inferior parietal cortex, striatum and thalamus, consistent with Hester et al (2004b) and previous neuroimaging studies of response inhibition (e.g., Garavan et al, 1999;Kelly et al, 2004;Liddle et al, 2001;Rubia et al, 2003;Watanabe et al, 2002). Errors of commission activated lateral frontal, midline, and insular areas also consistent with previous studies (Hester et al, 2004b;Holroyd et al, 2004;Ullsperger and Von Cramon, 2003;Ridderinkhof et al, 2004;Kiehl et al, 2000).…”
Section: Discussionsupporting
confidence: 77%
“…Participants performed the FWorking Memory Inhibitory Task_ (WMI task, Hester et al, 2004b), which comprises a Sternberg verbal WM task embedded in a GO/NOGO task. The task was programmed and displayed using E-prime 1.1 (Psychology Software Tools).…”
Section: Task Designmentioning
confidence: 99%
See 3 more Smart Citations